2018
DOI: 10.1186/s12891-018-2346-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential protein expression in human knee articular cartilage and medial meniscus using two different proteomic methods: a pilot analysis

Abstract: BackgroundProteomics is an emerging field in the study of joint disease. Our two aims with this pilot analysis were to compare healthy human knee articular cartilage with meniscus, two tissues both known to become affected in the osteoarthritic disease process, and to compare two mass spectrometry (MS)-based methods: data-dependent acquisition (DDA) and data-independent acquisition (DIA).MethodsHealthy knee articular cartilage taken from the medial tibial condyle and medial meniscus samples taken from the body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…This prompted us to compare our list of calcification-contained proteins to those reported to be present in connective tissues. For this, we compiled proteomic datasets previously reported to produce three lists of entries for (i) tendon [22,23,24,25,26], (ii) bone [27,28], and (iii) cartilage [29,30]. As the compiled and compared datasets were acquired from samples of different species, we relied on the gene names extracted from Uniprot [31] to perform the comparison between sample types.…”
Section: Resultsmentioning
confidence: 99%
“…This prompted us to compare our list of calcification-contained proteins to those reported to be present in connective tissues. For this, we compiled proteomic datasets previously reported to produce three lists of entries for (i) tendon [22,23,24,25,26], (ii) bone [27,28], and (iii) cartilage [29,30]. As the compiled and compared datasets were acquired from samples of different species, we relied on the gene names extracted from Uniprot [31] to perform the comparison between sample types.…”
Section: Resultsmentioning
confidence: 99%
“…The glycoprotein myocilin showed the highest mean intensity in lateral ref menisci compared to lateral OA menisci. We previously identified myocilin in both articular cartilage and meniscus, found to be more abundant in the meniscus than articular cartilage 20 . In addition, a previous proteomic study reported higher expression of myocilin in synovial fluid from healthy controls compared to individuals with meniscal injuries or pathologies 21 , which is consistent with our findings.…”
Section: Osteoarthritis Andcartilagementioning
confidence: 99%
“…Separation was performed on 75 μm × 25 cm, Acclaim Pepmap™ RSLC C18 capillary columns packed with 2 μm particles (ThermoFisher Scientific). The on-line reversed-phase separation was performed using a flow rate of 300 nL/min and a linear binary gradient for 85 min [ 32 ]. A spray voltage of + 2000 V was used with a heated ion transfer setting of 275 °C for desolvation.…”
Section: Methodsmentioning
confidence: 99%